2010
DOI: 10.1017/s146342361000006x
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare staffs perceptions of using interpreters: a qualitative study

Abstract: Aim: The aim of this study was to describe how healthcare professionals experience and perceive the use of interpreters in their contacts with patients with whom they do not share a common language. Background: Language barriers lead to poor-quality care and fewer medical contacts. To avoid language barriers and their consequences, interpreters are recommended. However, communicating through an interpreter can be difficult. To develop effective interpreter service it is important to study healthcare staff's pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
62
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(74 citation statements)
references
References 14 publications
10
62
2
Order By: Relevance
“…Interpreters did not recommend telephone interpretation because of the lack of body language and the low quality of technical equipment, which is in accordance with previous studies of Arabic-speaking migrants , Bosnian/Croatian/Serbian-speaking migrants (Hadziabdic et al, 2009b) and different kinds of healthcare staff (Hadziabdic et al, 2010). However, the second new finding of this study was that most of the interpreters who were on the agencies' telephone priority lists were employed by agencies who only invest small sums in interpreters' authorisation, training development and opportunities, so many telephone interpreters had low-quality language skills and lacked a professional attitude, which negatively affected communication as well as patient safety and quality of healthcare.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Interpreters did not recommend telephone interpretation because of the lack of body language and the low quality of technical equipment, which is in accordance with previous studies of Arabic-speaking migrants , Bosnian/Croatian/Serbian-speaking migrants (Hadziabdic et al, 2009b) and different kinds of healthcare staff (Hadziabdic et al, 2010). However, the second new finding of this study was that most of the interpreters who were on the agencies' telephone priority lists were employed by agencies who only invest small sums in interpreters' authorisation, training development and opportunities, so many telephone interpreters had low-quality language skills and lacked a professional attitude, which negatively affected communication as well as patient safety and quality of healthcare.…”
Section: Discussionsupporting
confidence: 85%
“…However, the second new finding of this study was that most of the interpreters who were on the agencies' telephone priority lists were employed by agencies who only invest small sums in interpreters' authorisation, training development and opportunities, so many telephone interpreters had low-quality language skills and lacked a professional attitude, which negatively affected communication as well as patient safety and quality of healthcare. Despite this, across healthcare settings there is reliance on telephone interpretation (Hadziabdic et al, 2010, Dowbor et al, 2015 due to positive impacts on access to healthcare (Dowbor et al, 2015). Staff in the healthcare service need to be aware of the opportunity to learn from the interpreters' own perspectives when planning to sign a contract with an interpreter agency, in order that they specify requirements for a high level of competence from interpreters for both face-to-face and telephone interpretation, in accordance with the existing Swedish law (SFS, 2007:1091) and the International Code of Ethics for Medical Interpreters (IMIA, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using professional interpreters was recommended, as they have good knowledge of medical terms and systems and can facilitate effective and productive communication. This phenomenon is not unique to Canada (Hadziabdic et al, 2009(Hadziabdic et al, , 2010(Hadziabdic et al, , 2011. Moreover, studies in the United Kingdom and Sweden have shown that effectiveness of interpretation services is influenced by ethnocultural factors (Hadziabdic et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…Rather, language interpretation is framed in a rights-based discourse, where it is suggested as a way to overcome barriers and promote equality by the law. Speaking particularly of health care, language interpretation is proposed as a way to increase patient participation and promote equal treatment and care (Hadziabdic et al 2010).…”
Section: Introductionmentioning
confidence: 99%